2013
DOI: 10.1513/annalsats.201305-124oc
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evidence of Intrapulmonary Anastomoses by Three-Dimensional Reconstruction in Severe Bronchopulmonary Dysplasia

Abstract: Rationale: Bronchopulmonary dysplasia (BPD) is the chronic lung disease of infancy that occurs in premature infants after oxygen and ventilator therapy for acute respiratory disease at birth. Despite improvement in current therapies, the clinical course of infants with BPD is often characterized by marked hypoxemia that can become refractory to therapy. Preacinar anatomic and functional communications between systemic and pulmonary vascular systems has been established in fetal lungs, but whether increased int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 37 publications
5
53
0
Order By: Relevance
“…[3][4][5][6] In these infants, we found prominent anastomotic connections between bronchial arteries and pulmonary arteries as well as markedly dilated bronchial and pulmonary veins. These findings suggest the presence of intrapulmonary shunt vessels that may also contribute to hypoxia.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…[3][4][5][6] In these infants, we found prominent anastomotic connections between bronchial arteries and pulmonary arteries as well as markedly dilated bronchial and pulmonary veins. These findings suggest the presence of intrapulmonary shunt vessels that may also contribute to hypoxia.…”
mentioning
confidence: 73%
“…Histologic evidence of shunt vessels were not found in infants who died from nonrespiratory causes, as we have previously shown (Figure, D). 3 …”
Section: Resultsmentioning
confidence: 99%
“…The pulmonary circulation in BPD is characterized by abnormal growth, including decreased vascular branching, an altered pattern of vascular distribution within the interstitium, and persistent precapillary arteriovenous anastomotic vessels (3,(10)(11)(12)(13)(14). Although the pathogenesis of BPD is complex and multifactorial (15), preclinical studies have shown that early disruption of angiogenesis in the developing lung impairs alveolarization and causes sustained abnormalities of lung structure that mimic clinical BPD (16)(17)(18).…”
Section: At a Glance Commentarymentioning
confidence: 99%
“…69 IAAV are small connecting vessels that shunt deoxygenated blood into the pulmonary venous circulation and thus prevent gas exchange at the alveolar-capillary interface (Fig. 2).…”
Section: Pathophysiology Of Ph In Bpdmentioning
confidence: 99%